ASSESSMENT OF HEALTH CADRES’ KNOWLEDGE ON DANGER SIGNS OF PREGNANCY - Restuning Widiasih; Ida Maryati; Yanti Hermayanti; Tetti Solehati (Journal of Maternity Care and Reproductive Health, 2018)
Maternal mortality rates (MMR) in Indonesia have not reached the target of Sustainable Development Goals (SDGs). The Indonesian government has established a Delivery Planning and Complication Prevention program (P4K) that focuses on community empowerment including health cadres. Health cadres have a significant role in preventing of maternal mortality in the maternal periods (pregnancy, childbirth, and postpartum), including early detection of danger signs of pregnancy. However, there is limited research in Indonesia that examines cadre’s knowledge about the danger signs of pregnancy in detail. This study aimed to assess cadres’ knowledge of danger signs in the maternal period especially in pregnancy. This research is a quantitative descriptive study. The study was conducted in Tempuran sub-district, Karawang regency, West Java. 48 cadres were involved in this study. Respondents filled in questionnaires about the danger signs of pregnancy. The results showed that the majority of cadres understood danger signs in pregnancy. Premature rupture of membranes (91.6%) and convulsions (91.6%) were danger signs that best known by cadres. While the signs of vaginal discharge (8%), heartburn (8%), and prolonged labor (4%) were little known by cadres as part of danger signs of pregnancy. The level of cadre knowledge about danger signs of pregnancy is varied. This research is the baselines information that may useful for program developments in relation to increase cadre capacity in preventing maternal mortality in the maternal periods.Keywords: Cadres, knowledge, danger signs of pregnancy